Application of microalgae Chlamydomonas applanata M9V and Chlorella vulgaris S3 for wheat growth promotion and as urea alternatives - Sido, Mekiso Yohannes; Tian, Yinping; Wang, Xiaogai; Wang, Xinzhen (Frontiers in Microbiology, 2022)
Excessive use of chemical fertilizers to meet the global food demand has caused extensive environmental pollution. Microalgae can be used to enhance agricultural crop production as a potential sustainable and eco-friendly alternative. In this study, Chlamydomonas applanata M9V and Chlorella vulgaris S3 were isolated from the soil and mass-cultured for use as microalgal fertilizers. The influence of microalgae M9V and S3 on the growth of wheat (Triticum aestivum L.) and soil properties was evaluated and compared with that of chemical urea fertilizer. A pot experiment was conducted with six treatments, i.e., living M9V (M9VL), dead M9V (M9VD), living S3 (S3L), dead S3 (S3D), urea fertilizer (urea), and control without fertilizer (control). M9VL was found to have the best effect on wheat growth promotion, followed by M9VD and S3D. In addition, M9VL resulted in the highest enhancement of shoot fresh weight (166.67%, 125.68%), root dry weight (188.89%, 77.35%), leaf length (26.88%, 14.56%), root length (46.04%, 43.93%), chlorophyll a (257.81%, 82.23%) and chlorophyll b contents (269.00%, 247.27%) comparing to the control and urea treatments, respectively. Moreover, all microalgal fertilizer treatments increased soil organic matter (SOM) by 1.77‒23.10%, total carbon (TC) by 7.14‒14.46%, and C:N ratio by 2.99‒11.73% comparing to the control and urea treatments. Overall, this study provided two microalgae strains, M9V and S3, that could promote wheat growth and improve soil properties, thus highlighting the use of microalgae as biofertilizers to reduce the use of chemical fertilizers and promoting sustainable agricultural production.